Training on Household Organic Waste Utilization for Maggot Cultivation as an Effort to Increase Environmental Awareness and Family Income in Perum Mustika Tigaraksa, Tangerang - Suhartono; Purnawan Lesna; Edi Hidayat Cecep; Riyanto Slamet (The International Journal of Education Management and Sociology, 2025)
The training on the utilization of household organic waste for maggot cultivation was conducted as an effort to increase environmental awareness while creating opportunities to improve family income in Perum Mustika Tigaraksa, Tangerang. This activity was motivated by the increasing volume of unutilized organic waste and the community’s low level of knowledge regarding circular economy-based waste management. The training method employed a participatory approach through several stages: socialization, direct demonstration, technical assistance, and evaluation. Participants consisted of local residents, particularly housewives and youths, who were trained to process kitchen waste into feed media for Black Soldier Fly (BSF) larvae or maggots. The results showed an increase in participants’ knowledge and skills in sorting organic waste, cultivating maggots, and utilizing the products as animal feed and organic compost. Moreover, the program successfully fostered public awareness of environmentally friendly waste management and opened new household-based business opportunities with the potential to increase family income. Overall, this activity effectively integrated ecological, educational, and economic aspects while supporting the government’s sustainable waste management program at the community level.